Comparative Effectiveness of Generic Atorvastatin and Lipitor® in Patients Hospitalized with an Acute Coronary Syndrome. Issue 4 (April 2016) - Jackevicius, Cynthia A.; Tu, Jack V.; Krumholz, Harlan M.; Austin, Peter C.; Ross, Joseph S.; Stukel, Therese A.; Koh, Maria; Chong, Alice; Ko, Dennis T.
Abstract : Background: Although generic medications are approved based on bioequivalence with brand‐name medications, there remains substantial concern regarding their clinical effectiveness and safety. Lipitor ®, available as generic atorvastatin, is one of the most commonly prescribed statins. Therefore, we compared the effectiveness of generic atorvastatin products and Lipitor ® . Methods and Results: We conducted a population‐based cohort study, using propensity score matching to minimize potential confounding of patients ≥65 years, discharged alive after acute coronary syndrome (ACS) hospitalization between 2008 and 2012 in Ontario, Canada, who were prescribed Lipitor ® or generic atorvastatin within 7 days of discharge. The primary outcome was 1‐year death/recurrent ACS hospitalization. Secondary outcomes included hospitalization for heart failure, stroke, new‐onset diabetes, rhabdomyolysis, and renal failure. In the 7863 propensity‐matched pairs (15 726 patients), mean age was 76.9 years, 56.3% were male, 87.6% had myocardial infarction, and all patients had complete follow‐up. At 1 year, 17.7% of those prescribed generic atorvastatin and 17.7% of those prescribed Lipitor ® experienced death or recurrent ACS (hazard ratio, 1.00; 95% CI, 0.93–1.08; P =0.94). No significant differences in rates of secondary outcomes between groups were observed. Prespecified subgroup analyses by age, sex, diabetes, atorvastatin dose, or admission diagnosis found no outcome difference between groups. Conclusions: Among older adults discharged alive after ACS hospitalization, we found no significant difference in cardiovascular outcomes or serious, infrequent side effects in patients prescribed generic atorvastatin compared with those prescribed Lipitor ® at 1 year. Our findings support the use of generic atorvastatin in ACS, which could lead to substantial cost saving for patients and health care plans without diminishing population clinical effectiveness.